Beyond Survival: Policies for Academic Revitalization in An Uncertain Environment - Fleming, Thomas (Canadian Journal of Higher Education, 1980)
Confronted with growing public skepticism concerning the value of higher education, the spiralling costs of educational services and an overall mood of economic retrenchment and uncertainty, academic organizations face the need to develop policies to maintain their institutional health under increasingly difficult conditions. This discussion briefly describes educational developments since 1945 - particularly those factors which have contributed to the present climate of adversity - and explores how these historical forces have altered the complexion of university governance. Special attention is directed toward a review of proposals for academic revitalization found in recent literature and an examination of policies currently under consideration by senior administrators at univer- sities in Western Canada.